Comparative Analysis of Formal and Informal Speech Genres in Modern Uzbek (A Case Study of Contemporary Uzbek Language) - Yusupaliyev Bekzod Nematovich; Jamoldinova Sarvinoz Abrorbek qizi (International Journal Of Literature And Languages, 2026)
This article examines the comparative features of formal and informal speech genres in modern Uzbek from a functional and sociolinguistic perspective. The study analyzes lexical, grammatical, and pragmatic characteristics of both genres based on authentic contemporary language data. The findings indicate that formal speech is marked by standardization, structural complexity, and institutional orientation, whereas informal speech demonstrates flexibility, emotional expressiveness, and interpersonal focus. The research also reveals that ongoing digitalization and social transformation in Uzbekistan are contributing to the emergence of hybrid communicative forms. The results confirm that speech genres function as socially conditioned and relatively stable discourse patterns, consistent with the theoretical framework proposed by Mikhail Bakhtin.